Selective Estrogen Receptor Modulators 4-Hydroxytamoxifen and Raloxifene Impact the Stability and Function of SRC-1 and SRC-3 Coactivator Proteins - Lonard, David M. (American Society for Microbiology, 2004)
Proteasome-mediated protein degradation has been implicated in playing a role in nuclear receptor-mediated gene expression; inhibition of the proteasome impairs the transcriptional activity of estrogen receptor α (ERα) and most other nuclear receptors. This coincides with blockage of agonist-dependent degradation of the receptor and elevation of the steady-state levels of SRC family coactivators and CBP. Here, we examined the effects that different ERα ligands have on coactivator protein steady-state levels and demonstrate that the selective ER modulators (SERMs) 4-hydroxytamoxifen (4HT) and raloxifene are able to elevate SRC-1 and SRC-3 protein levels. Using the HeLa cell line, we show that this effect is ERα dependent. Consistent with the observed increase in coactivator protein levels, we were also able to observe an increase in the transcriptional activity of other nuclear receptors in SERM-treated cells. Information presented here demonstrates an unexpected consequence of SERM treatment, which could help further define the complex tissue responses to 4HT and raloxifene, and suggests that these ligands can have a broad biological action, stimulating the transcriptional activity of other nuclear receptors.